Six-minute step test performance in asymptomatic adults - Riya Kalra; Kanu Goyal; Manu Goyal; Hina Vaish (PAGEPress Publications, 2023)
The objectives of this study were i) to measure a six-minute step test (6MST) in asymptomatic adults; ii) to determine the applicability of Arcuri et al.'s reference equation to Indian adults; iii) to develop a prediction equation for Indian adults. 110 adult males and females aged 18-40 years were recruited for this prospective cross-sectional study conducted in India. Participants underwent 6MST. Applicability was assessed by comparing the findings of the 6MST with the values derived from Arcuri et al.'s predicted equations using the Bland-Altman plot. A multiple regression analysis was used to develop the prediction equation. The mean±SD six-minute step count was 159.42±17.60 steps and 150.78±14.39 steps in males and females respectively. The 6MST for males can be determined by males (steps)=204.371-1.521×age(years) and females (steps)=179.567-1.06×age (years). Arcuri et al.'s equation cannot be used to predict 6MST in Indian adults. Region-specific equations are useful to assess the values.